Effects of midlatitude westerlies on the paleoproductivity at the Agulhas Bank slope during the penultimate glacial cycle: Evidence from coccolith Sr/Ca ratios. (2nd July 2014) - Mejía, Luz María; Ziveri, Patrizia; Cagnetti, Marilisa; Bolton, Clara; Zahn, Rainer; Marino, Gianluca; Martínez‐Méndez, Gema; Stoll, Heather
Abstract: Modern primary productivity on the Agulhas Bank, off South Africa, has been proposed to be linked to the midlatitude westerlies. A paleoproductivity record from this area may therefore resolve temporal changes in the westerly dynamics. Accordingly, we produced a coccolith Sr/Ca‐based paleoproductivity record from core MD96‐2080 (Agulhas Bank slope) during the penultimate glacial‐interglacial cycle. Deriving the productivity signal from Sr/Ca requires a correction for a temperature effect, here constrained using Mg/Ca sea surface temperatures from the foraminifer Globigerina bulloides from core MD96‐2080. Phases of depressed productivity coincided with periods of stratification in the same core, indicated by high relative abundances of the coccolithophore Florisphaera profunda and with low relative abundances of the upwelling indicator G . bulloides in the nearby Cape Basin. These observations collectively suggest that productivity was regulated by upwelling throughout this region. We infer that, as in the present, periods of low productivity result from a more northerly position of the westerlies, potentially accompanied by subtropical front displacements, and blockage of upwelling promoting easterlies. Productivity minima also coincide with periods of increased ice‐rafted detritus (IRD) deposition on the Agulhas Plateau, which also indicates extreme northward positions of the westerlies. The influence of the westerlies appears to be obliquity conditioned, as productivity minima (and IRD maxima) occur during low‐obliquity intervals. The dynamic connection between productivity and the westerlies is supported by coeval salinity changes in the South Indian Gyre that likewise respond sensitively to a poleward contraction of the westerlies. Key Points: Coccolith Sr/Ca reveals productivity on Agulhas Bank slope Southern Hemisphere westerlies controlled paleoproductivity on the Agulhas Bank Productivity records from the area provide information on westerly dynamics